2000
DOI: 10.1162/089892900562129
|View full text |Cite
|
Sign up to set email alerts
|

Motor Area Activity During Mental Rotation Studied by Time-Resolved Single-Trial fMRI

Abstract: Abstract& The functional equivalence of overt movements and dynamic imagery is of fundamental importance in neuroscience. Here, we investigated the participation of the neocortical motor areas in a classic task of dynamic imagery, Shepard and Metzler's mental rotation task, by time-resolved single-trial functional Magnetic Resonance Imaging (fMRI). The subjects performed the mental-rotation task 16 times, each time with different object pairs. Functional images were acquired for each pair separately, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
188
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(215 citation statements)
references
References 27 publications
22
188
0
5
Order By: Relevance
“…Activations in the present study also included the right posterior parietal cortex, an area, whose implication has been found in most studies testing mental transformations, especially of nonbodily objects [i.e. Harris et al, 2000;Jordan et al, 2001;Podzebenko et al, 2002;Richter et al, 2000]. Finally, frontal activations found in the present study have also been revealed in previous mental transformation studies, especially when using stimuli that depict graspable nonbodily objects or human bodies [Georgopoulos et al, 1989;Kosslyn et al, 1994].…”
Section: Mental Own Body Transformations Depend On the Rotation Anglesupporting
confidence: 82%
“…Activations in the present study also included the right posterior parietal cortex, an area, whose implication has been found in most studies testing mental transformations, especially of nonbodily objects [i.e. Harris et al, 2000;Jordan et al, 2001;Podzebenko et al, 2002;Richter et al, 2000]. Finally, frontal activations found in the present study have also been revealed in previous mental transformation studies, especially when using stimuli that depict graspable nonbodily objects or human bodies [Georgopoulos et al, 1989;Kosslyn et al, 1994].…”
Section: Mental Own Body Transformations Depend On the Rotation Anglesupporting
confidence: 82%
“…Although it is generally agreed that the parietal cortex is involved in the mental rotation process, there is considerable disagreement about interhemispheric activation differences. For Shepard-Metzler-like stimuli most studies have reported bilateral parietal activation (Cohen et al, 1996;Richter et al, 1997Richter et al, , 2000Jordan et al, 2001), while experiments using other stimuli demonstrated predominance of either the left (Alivisatos and Petrides, 1997) or the right hemisphere (Harris et al, 2000;Yoshino et al, 2000) or no distinct difference (Tagaris et al, 1998;Lamm et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…From these results it was hypothesized that subjects "mentally rotated" the mental image of one object along a trajectory until it had the same orientation as the other object and then compared both for congruency. Based on this study, a number of experiments investigating the brain responses underlying mental rotation processes have been performed, using electrophysiological methods, positron emission tomography and functional magnetic resonance imaging (fMRI) (Cohen et al, 1996;Alivisatos and Petrides, 1997;Tagaris et al, 1997Tagaris et al, , 1998Richter et al, 1997Richter et al, , 2000Kosslyn et al, 1998;Carpenter et al, 1999;Harris et al, 2000;Yoshino et al, 2000;Jordan et al, 2001;Lamm et al, 2001;Vingerhoets et al, 2001Vingerhoets et al, , 2002. Although it is generally agreed that the parietal cortex is involved in the mental rotation process, there is considerable disagreement about interhemispheric activation differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Dynamic" or "spatial" mental imagery involves spatial relations (e.g., location) and the mental manipulation or transformation of images. This type of mental imagery, which is found in tasks entailing mental rotation or orientation discrimination, is strongly linked to motor processes (Vingerhoets et al, 2002;Wexler et al, 1998c), and seems to depend on the dorsal stream pathway (Farah, 1989;Podzebenko et al, 2002) and on the brain structures underlying the procedural system: Broca's area (Jordan et al, 2001;Podzebenko et al, 2002); premotor regions, including both lateral premotor cortex and the SMA (Cohen et al, 1996; Jordan et al, 2001;Kosslyn et al, 1998;Podzebenko et al, 2002;Richter et al, 2000;Tagaris et al, 1997); the basal ganglia (Podzebenko et al, 2002); the cerebellum (Ivry and Fiez, 2000;Podzebenko et al, 2002); and parietal cortex (Bestmann et al, 2002;Harris et al, 2000;Podzebenko et al, 2002), including the supramarginal gyrus (Harris et al, 2000;Podzebenko et al, 2002). In contrast, "static" or "visual" imagery, which involves imaging static objects or their features (e.g., color, form), is linked to the perception and processing of this type of information, to occipital and temporal regions, and to the ventral stream pathway (which is closely related to declarative memory; see above) (Farah, 1989;Farah, 1995;Goodale, 2000).…”
mentioning
confidence: 99%